NFS illustrated - Callaghan, Brent (Addison-Wesley professional computing series., 2000)
"Written for programmers creating NFS-based applications, network engineers creating new implementations of NFS, and network managers, NFS Illustrated promotes a thorough understanding of the protocol through extensive diagrams and real protocol traces that show NFS in action."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved.